A contribuição da internet para a espetacularização da notícia - Mora, Marcelo de Souza (2010)
As studied the mode of production of online journalism, the goal is show how this contributes to convert in spectacular the news, at a time when, increasingly, the technology becomes an ally of the producers and distributors of information and the image is needed harder. Therefore, it was necessary a closer look at the subtleties that separate journalism and entertainment and at to the sensationalism in the press in this work. However, do not come to any conclusion in this study if there was an empirical basis to substantiate this research. This daily practice experience in webjournalism that was allowed to be made questions that could point to that direction so it goes